Synergistic effects of trastuzumab and gambogic acid on MDA-MB-453 breast cancer cell line - Abdullah Alpkan; Murat Cankaya (Polskie Towarzystwo Farmaceutyczne, 2023)
Trastuzumab is one of the most commonly used monoclonal antibodies in the treatment of breast cancer. It is effective because it binds to the HER2 receptor and inhibits the signaling pathways for proliferation and metastasis. However, intrinsic or acquired resistance resulting from the various signaling pathways of heterogeneous breast cancer reduces its efficacy. To increase its efficacy, it is combined with different agents in the treatment. In this study, the synergistic effect of the combination of trastuzumab and gambogic acid on the breast cell line MDA-MB -453 was investigated in vitro. At the end of 12-, 24-, 48-, and 72-hour incubation, their antiproliferative effects were determined by XTT method. Combination Index (CI) values of the study were calculated using CompuSyn.exe software. The highest synergistic effect was obtained with 12.5 µg/mL trastuzumab + 1.25 µM gambogic acid (CI-4) at the 72nd hour. The activity of the antioxidant enzyme catalase (CAT) was also measured for the applications. We observed that combination of trastuzumab and gambogic acid decreased CAT activity at 24, 48 and 72nd hours. It was concluded that gambogic acid may be a good candidate for combination with other agents in targeted drug design.